Comparison of childhood adversities and their possible consequences in Poland and Germany - Hardt, Jochen; Dragan, Malgorzata; Schultz, Sonja; Schier, Katarzyna (Journal of public health, 2011)
Aim How children grow up differs from country to country. The aim of the present investigation was to compare childhood experiences, family characteristics and psychological features during the post-World War II period in Poland and Germany. Subject and methods A questionnaire regarding various childhood experiences and family circumstances was administered to two samples, one each in Poland and Germany ( n = 500 each) via the Internet. Comparisons between Poland and Germany were performed using analysis of variance (ANOVA) and χ 2 tests, and logistic regressions were performed to compare the effects of risk factors. Results Probands from Poland described almost all aspects of their lives, their families and their childhoods as having been better than did probands from Germany. Risk factors for suicide attempts were childhood physical abuse, and for alcohol abuse gender and childhood sexual abuse in both countries. Conclusion There is some evidence for idealisation of the past in Poland, which might be due to the fact that almost 90% of the Poles were Christians. Germans seem to be more realistic in their views of the past but possibly deny their personal weaknesses.